2015
DOI: 10.1063/1.4922804
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent energy levels of methylammonium lead iodide perovskite

Abstract: Temperature dependent energy levels of methylammonium lead iodide are investigated using a combination of ultraviolet photoemission spectroscopy and optical spectroscopy. Our results show that the valence band maximum and conduction band minimum shift down in energy by 110 meV and 77 meV as temperature increases from 28 C to 85 C. Density functional theory calculations using slab structures show that the decreased orbital splitting due to thermal expansion is a major contribution to the experimentally observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
149
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 40 publications
25
149
1
2
Order By: Relevance
“…Note that, for the HEAT1 process, upon heating from 80 to 140 K, the ∼1.85-eV emission peak experiences a blue shift of 0.08 eV, which is typical behavior due to the positive temperature coefficient of bandgap in lead halide perovskites (24). However, at 160 K, the emission peak shifts back to 1.77 eV, and, upon further heating to 400 K, it experiences a blue shift of 0.14 eV.…”
Section: Significancementioning
confidence: 92%
“…Note that, for the HEAT1 process, upon heating from 80 to 140 K, the ∼1.85-eV emission peak experiences a blue shift of 0.08 eV, which is typical behavior due to the positive temperature coefficient of bandgap in lead halide perovskites (24). However, at 160 K, the emission peak shifts back to 1.77 eV, and, upon further heating to 400 K, it experiences a blue shift of 0.14 eV.…”
Section: Significancementioning
confidence: 92%
“…17,22,26,[54][55][56] We mention that the el-ph renormalization effects (which tend to reduce the band gap with increasing temperature) are not included in our calculation as we have mentioned earlier. As a reference, the el-ph renormalization is about 0.15 eV 59 in ZnO due to zero-point vibrations.…”
Section: 3651mentioning
confidence: 99%
“…10 Previous theoretical studies have shown a positive band gap deformation potential (a V = ∂E g /∂ln V ) of these materials. 61 We would like to point out, however, that one cannot compare directly the calculated volume-dependent band gap with the measured temperature-dependent band gap [54][55][56] by simply taking into account the thermal expansion effects. This is because the temperature-dependent el-ph effects (which tend to reduce the band gap with increasing temperature 62 ) cancel out partially the volume deformation effects (which tend to increase the band gap with increasing temperature as a result of thermal expansion and a positive deformation potential).…”
Section: 3651mentioning
confidence: 99%
See 1 more Smart Citation
“…This is conflated with thermal lattice expansion, which also affect the band gap (larger lattice parameters give larger band gaps), and the combination of the two effects may explain why observed band gaps in MAPbI 3 increase with temperature. [25][26] More accurate calculations of electronic and opto-electronic properties of these structural models may be provided by many-body perturbation theory, 27-28 but we expect the trends discussed here to be robust. Our HERFD XAS is sensitive to both lattice parameters (demonstrated with P3 vs.…”
mentioning
confidence: 99%